2021
DOI: 10.1016/j.ynstr.2021.100361
|View full text |Cite
|
Sign up to set email alerts
|

Is neuroticism really bad for you? Dynamics in personality and limbic reactivity prior to, during and following real-life combat stress

Abstract: The personality trait of neuroticism is considered a risk factor for stress vulnerability, putatively via its association with elevated limbic reactivity. Nevertheless, majority of evidence to date that relates neuroticism, neural reactivity and stress vulnerability stems from cross-sectional studies conducted in a “stress-free” environment. Here, using a unique prospective longitudinal design, we assessed personality, stress-related symptoms and neural reactivity at three time points over the course of four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Further, study by Gelernter et al found CRHR1 significantly associated with re-experiencing PTSD symptoms [42] and also maximum habitual alcohol intake [43]. This gene is also involved in hippocampal neurogenesis [40] while reduced hippocampal activation is associated with elevated neuroticism [44]. This makes CRHR1 a good lead candidate to be followed in future studies to understand the molecular processes impacted by genetic variation underlying a range pf psychiatric traits including neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…Further, study by Gelernter et al found CRHR1 significantly associated with re-experiencing PTSD symptoms [42] and also maximum habitual alcohol intake [43]. This gene is also involved in hippocampal neurogenesis [40] while reduced hippocampal activation is associated with elevated neuroticism [44]. This makes CRHR1 a good lead candidate to be followed in future studies to understand the molecular processes impacted by genetic variation underlying a range pf psychiatric traits including neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of "healthy neuroticism", emphasize the functional benefits of vigilance and worry in threatening situations [70]. Studies have suggested that high levels of neuroticism may actually boost stress resilience [71] and promote recovery after highly stressful periods [72]. Although neuroticism seems related to less problem-solving and to some inappropriate problem-solving strategies, neuroticism has also been related to more support-seeking [73].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals with high levels of neuroticism are more inclined to adopt negative cognitive appraisal, considering family incivility (i.e., the stressor) threatening ( Schneider, 2004 ), eventually leading individuals to adopt negative coping strategies (e.g., cyberbullying perpetration), to alleviate their negative emotions. A recent biological experiment also showed that high neuroticism can increase individuals’ reactivity of limbic system and decrease their tolerance to stressors or aversive stimuli, so that highly neurotic individuals are always disturbed by negative emotions and adopt negative coping strategies ( Magal et al, 2021 ). Our study reflects individual differences among victims suffering from family incivility, and neuroticism plays an important role in this moderated mediation model.…”
Section: Discussionmentioning
confidence: 99%